(r, p)-absolutely summing operators on the space C (T, X) and applications. (25th November 2001) - Popa, Dumitru
Abstract : We give necessary and sufficient conditions for an operator on the spaceC   ( T, X ) to be( r, p ) -absolutely summing. Also we prove that the injective tensor product of an integral operator and an( r, p ) -absolutely summing operator is an( r, p ) -absolutely summing operator.